Inuit Toponyms, Territory Memory : A Study of the Inuinnait History - Béatrice Collignon (Anthropologie et Sociétés, 2003)
This paper studies the geographical dimension of the memory of the Inuit through the oral tradition of the Inuinnait (Copper Eskimo, Canadian Western Central Arctic). It analyses their toponymic system, collected in 1991-1992, in relation with the stories of their oral tradition, collected at three different periods of the 20th century (1914-1916, 1923-1924, 1958). There appears to be a tight link between space and time, as the memory of the Inuinnait articulates places and events. The territory of the stories covers entirely the territory named. However, the spatial distribution of the stories mentioning place names is irregular throughout the whole territory. The spatial dimension is a key element in the constitution of the memory of the Inuit. Some places play a specific role in the history-making process and, as such, they can be identified as « geosymbols », according to geographer Bonnemaison’s terminology. The identification of those geosymbols by the researcher is validated by recent local initiatives regarding the recognition of some places as « heritage sites ». La mémoire des Inuit est ici appréhendée dans sa dimension géographique. L’étude se concentre sur les Inuinnait (Eskimo du Cuivre, Arctique occidental canadien). L’approche analyse leur système toponymique, recueilli par l’auteur en 1991-1992, et ses relations avec les récits de leur tradition orale collectés à trois reprises au cours du XXe siècle : en 1914-1916, 1923-1924 et 1958. La relation étroite entre l’espace et le temps est mise en évidence, la mémoire des Inuinnait articulant étroitement les lieux et les événements. Les références territoriales des récits couvrent l’ensemble du territoire nommé, mais la distribution spatiale de ces histoires se révèle aléatoire. La dimension spatiale apparaît comme constitutive de larges pans de la mémoire Inuit. Reprenant le concept de « géosymboles » développé par le géographe Joël Bonnemaison, on entreprend ensuite d’identifier les lieux du territoire des Inuinnait qui pourraient être qualifiés ...